Puncture of thoracic lesions under sonographic guidance. - Afschrift, M (1982)
Thirty-six punctures of thoracic lesions have been performed with a compound B-scanner or a real-time linear-array scanner for guidance. Twenty-three fluid collections were punctured and aspiration biopsies were performed on 13 echogenic lesions. All the punctures were successful at the first attempt. No complications occurred. The results confirm the usefulness of sonography for guiding punctures of thoracic fluid effusions and solid masses. Usually a static B-scanner is sufficient, but when masses are small or surrounded by vital structures puncture may be controlled by a real-time scanner.